TRAINING ON PROCESSING PINEAPPLE FRUIT (Ananas comosus)INTO JAM FOR PKK WOMEN IN GAMPONG PEUNITI,BANDA ACEH: PELATIHAN PENGOLAHAN BUAH NANAS (Ananas comosus) MENJADI SELAI KEPADA IBU-IBU PKK GAMPONG PEUNITIKOTA BANDA ACEH - Puput Isnani; Abdul Malik; Muhammad Kamal Muda; Adil Azrial Akbar; Elvrida Rosa; Savitri (PT. ROCE WISDOM ACEH, 2024)
Pineapples are fruit plants commonly cultivated in tropical and subtropical regions. Pineapples possess distinct characteristics in terms of aroma, flavor, and color that are favored by many people. They contain carbohydrates, including sugars that can increase blood sugar levels. Pineapples have high water and fiber content, which can clean the mouth's surface and aid in digestion. The sugars in pineapples include glucose (2.32%), fructose (1.42%), and sucrose (7.89%). The acids found in pineapples are citric acid, malic acid, and oxalic acid, with citric acid being the most dominant, constituting 78% of total acids. The training activity on pineapple jam processing aims to enhance the knowledge of PKK (Family Welfare Movement) mothers in Peuniti Village about the process of producing pineapple-based food products. This activity took place in the courtyard of the Peuniti Village Head Office, Baiturrahman District, Banda Aceh City, and was attended by 20 PKK mothers from Peuniti Village. The implementation method of this activity involved several stages, including (1) socialization, (2) preparation, and (3) Training (demonstration) on pineapple jam processing. The results of this activity showed an improvement in the knowledge and skills of the participants. It is hoped that the knowledge and skills gained will serve as a foundation for meeting the nutritional needs of families while also initiating entrepreneurial efforts.